2020
DOI: 10.1017/wet.2020.59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dicamba rate and application parameters on protoporphyrinogen oxidase inhibitor-resistant and -susceptible Palmer amaranth (Amaranthus palmeri) control

Abstract: Throughout eastern Arkansas, Palmer amaranth resistant to protoporphyrinogen oxidase (PPO)-inhibiting herbicides (Group 14) has become widespread. Most PPO-resistant Palmer amaranth biotypes possess a target-site mutation, but a metabolic resistance mechanism to fomesafen (Group 14) has also been identified. Once metabolic resistance manifests, plants may also be tolerant to other herbicides and sites of action. To evaluate whether varying spray parameters affected control of PPO-resistant Palmer amaranth in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…At soybean harvest, a single application of dicamba at V4 or sequential applications reduced Palmer amaranth density as low as 2 or fewer plants m −2 compared with 5 or fewer plants m −2 with dicamba in a single application at R1 (Table 3). Similarly, Coffman et al (2020) reported Palmer amaranth densities of 7% and 19% of the nontreated control 21 d after dicamba application at 560 g ae ha −1 . The PPO inhibitors acifluorfen, lactofen, or fomesafen and fluthiacet applied in a single application at early SGS or in sequential applications were usually comparable and reduced Palmer amaranth density to not more than 15 plants m −2 .…”
Section: Palmer Amaranth Density and Biomassmentioning
confidence: 85%
“…At soybean harvest, a single application of dicamba at V4 or sequential applications reduced Palmer amaranth density as low as 2 or fewer plants m −2 compared with 5 or fewer plants m −2 with dicamba in a single application at R1 (Table 3). Similarly, Coffman et al (2020) reported Palmer amaranth densities of 7% and 19% of the nontreated control 21 d after dicamba application at 560 g ae ha −1 . The PPO inhibitors acifluorfen, lactofen, or fomesafen and fluthiacet applied in a single application at early SGS or in sequential applications were usually comparable and reduced Palmer amaranth density to not more than 15 plants m −2 .…”
Section: Palmer Amaranth Density and Biomassmentioning
confidence: 85%
“…The association of cover crops with herbicides in the integrated management of A. hybridus was also effective (Bunchek et al, 2020). Coffman et al (2021) observed that the application of dicamba could be an alternative for the control of the PPO-resistant A. palmeri; however, lower levels of control were observed in the PPO-resistant population than in the susceptible population. Other studies have reported the use of glufosinate to control Amaranthus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Combinations of glyphosate and dicamba controlled 90% to 100% of glyphosate‐resistant waterhemp, Palmer amaranth, and horseweed 8 . Applications of dicamba in dicamba‐resistant cotton controlled 88% to 90% of protoporphyrinogen oxidase (PPO)‐resistant Palmer amaranth in Arkansas at 21 days after treatment (DAT) 9 . Growers in Nebraska reported that the addition of dicamba to soybean herbicide programs resulted in improved weed control for 93% of growers surveyed 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Applications of dicamba in dicamba-resistant cotton controlled 88% to 90% of protoporphyrinogen oxidase (PPO)-resistant Palmer amaranth in Arkansas at 21 days after treatment (DAT). 9 Growers in Nebraska reported that the addition of dicamba to soybean herbicide programs resulted in improved weed control for 93% of growers surveyed. 10 Concurrent with the commercialization of dicamba for in-crop use over soybean in 2016, there was an increase in complaints for auxin damage on non-dicamba resistant soybean.…”
Section: Introductionmentioning
confidence: 99%